The Legal Framework of the Operation of Religious Associations in the Republic of Kazakhstan - ISKAKOVA, Indira E.; AMANDYKOVA, Saule k.; KOSZHANOV, Aitkul S.; MOMYSHEVA, Farhia S.; KARZHASOVA, Guldana B.; ZHAKSYBAYEVA, Gulnara M. (Journal of Advanced Research in Law and Economics, 2017)
The Republic of Kazakhstan is a secular state, which task is to prevent inter-religious conflict. To accomplish this, Kazakhstan is pursuing a policy of equality of all religions with activities governed by the laws of the republic. In this paper, the authors analyzed the Kazakhstani model of legal regulation of relations in the sphere of religion, as well as the gained experience. As a result, the specific legislative and practical measures have been isolated due to which the Republic of Kazakhstan established a peaceful interfaith and intra relations with religious associations. Thus, this article aims to fill the existing gap – analysis of the current legislation of the Republic of Kazakhstan, taking into account the innovations and improvements in recent years, made a religious policy of Kazakhstan unified, efficient and create favorable conditions for the further development of this sphere.